Ingratiation and the use of power in Malaysian secondary schools - Mat Zin, Sakinah; Nik Jaafar, Nik Fazlin Hiryati; Ngah, Nazlin Emieza; Ismail, Rusnah; Ibrahim, Norlaila; Jusoff, Kamaruzaman; Salleh, Asri (IDOSI Publications, 2011)
It is presumed that an ingratiating subordinate would acquire more rewards from a leader. When the leader is receptive to influence, subordinates would attempt to impress him/her by presenting themselves to be competent. This holds true for any type of organizations. The objective of this paper is to analyze principals’ exertion of power in Malaysian secondary schools and teachers’ ingratiatory strategy. This paper argues that generally, principals’ leadership in schools can be considered as authoritarian and that therefore, teachers are prone to employing ingratiation tactic in order to obtain the principal’s approval and receive favorable outcomes.